Tendencia nacional de la prevalencia y mortalidad por cáncer de tiroides con datos del Ministerio de Salud de Perú - Atamari Anahui, Noé (2019)
Introduction: The incidence of thyroid cancer has increased worldwide. Peru has few reports describing the national and regional epidemiology of thyroid cancer. Objective: The incidence of thyroid cancer has increased worldwide. Peru has few reports describing the national and regional epidemiology of thyroid cancer. Methods: A descriptive study of trends was conducted with secondary data obtained from a public information source in Peru. The ICD 10: C73.0 coding record was evaluated, by age group, year and region. The age-standardized prevalence (period 2005 to 2016) and mortality (period 2005 to 2015) were calculated by region and year of study. Results: In the 2005-2016 period, 19 513 cases of thyroid cancer were recorded. The age group with the highest frequency was 30 to 59 years (57.7%). The prevalence increased from 4.7 to 15.2 cases per 100 000 inhabitants in the period 2005-2016, with the coastal region showing the greatest increase. Likewise, 1596 deaths from thyroid cancer (period 2005 to 2015) were recorded, more frequently in those older than 60 years (75.5%). The age-standardized mortality rate increased from 0.67 in 2005 to 0.72 in 2015, being the highlands the one with the greatest increase. Conclusions: The prevalence of thyroid cancer increased and mortality remained constant in the period studied.